Prediction of rounding phenomenon at corner tips in large-area electron beam irradiation. (November 2016) - Shinonaga, Togo; Okada, Akira; Miyoshi, Tomoaki
Abstract: In large-area electron beam (EB) irradiation method, corner tip of workpiece is generally rounded since removal of material at the tip is done preferentially. Investigation of the shape change is necessary to clarify rounding phenomenon with irradiation of EB. In this study, the shape changes of corner tips were experimentally investigated by Scanning Electron Microscope (SEM) observation of the cross sections. Then, electron track analysis in the EB irradiation was conducted to clarify an electron concentration at the tip. Unsteady heat conduction analysis at the tip was also done with considering the EB concentration at the tip and an electron penetration effect into the surface. The shape changes were estimated by simulation of temperature distribution at the tips. Experimental results show that the curvature radius increases with shot number of EB. The estimated shape changes show quantitatively good agreement with the experimental ones. These results indicate that the rounding phenomenon at the tips by large-area EB irradiation can be predicted by our electron track and unsteady heat conduction analysis model. Highlights: Corner tip is rounded after large-area electron beam irradiation. Electron behavior near workpiece is simulated by electron track analysis. EB concentrates at corner tip due to concentration of magnetic fields near the tip. Shape change at tip is analyzed by unsteady heat conduction model. Rounding phenomenon at tip can be predicted by using our model.